2012
DOI: 10.1002/j.1532-2149.2012.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain following stroke: A prospective study

Abstract: Background: Post-stroke pain is common and affects the quality of life of stroke survivors, but the incidence and severity of headache, shoulder pain, other joint pain and central post-stroke pain following stroke still remain unclear. The aim of this prospective study was to determine the incidence and intensity of these different types of post-stroke pain. Methods: A total of 299 consecutive stroke patients, admitted to the Department of Neurology at Aarhus University Hospital, underwent a structured intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
3
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 26 publications
13
120
3
21
Order By: Relevance
“…Those with a history of tension-type or vascular headache are more likely to develop headache with or after stroke [121]. In general, post-stroke headache has been characterized as a tension-type headache that has a pressing quality, and is not aggravated by movement [33,122]. …”
Section: Post Stroke Headachementioning
confidence: 99%
See 2 more Smart Citations
“…Those with a history of tension-type or vascular headache are more likely to develop headache with or after stroke [121]. In general, post-stroke headache has been characterized as a tension-type headache that has a pressing quality, and is not aggravated by movement [33,122]. …”
Section: Post Stroke Headachementioning
confidence: 99%
“…Headache at stroke onset is shown to be predictive of headache at 6 months post-stroke [33]. Those with a history of tension-type or vascular headache are more likely to develop headache with or after stroke [121].…”
Section: Post Stroke Headachementioning
confidence: 99%
See 1 more Smart Citation
“…However, cerebral infarction was detected in 30% of the patients. Considering that cerebral infarction and ischemia can be causes of headache and dizziness, headache with infarction or severe ischemia should be classified as symptomatic MMD [9,10,11]. If a different treatment strategy can be applied to asymptomatic MMD from symptomatic disease, the definition should be strictly limited.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012 Hansen et al [12] proposed that patients suffering from DRS could be identified based on the following criteria [3,5]:…”
Section: Introductionmentioning
confidence: 99%